Answer:
Z = -2
Step-by-step explanation:
Answer:
=x⁴−x³−14x²
Step-by-step explanation:
<h3>Let's simplify step-by-step.</h3>
x²(3x²+5x−4)−2x²(x²+3x+5)
<h3>Distribute:</h3>
=(x²)(3x²)+(x²)(5x)+(x²)(−4)+−2x⁴+−6x³+−10x²
=3x⁴+5x³+−4x²+−2x⁴+−6x³+−10x²
<h3>Combine Like Terms:</h3>
=3x⁴+5x³+−4x²+−2x⁴+−6x³+−10x²
=(3x⁴+−2x⁴)+(5x³+−6x³)+(−4x²+−10x²)
=x⁴+−x³+−14x²
<h3>ANS-</h3>
=x⁴−x³−14x²
Answer:
1. MIGHT be 16 1/2
Step-by-step explanation:
causse 2/3 / 4/9 = 1 1/2
1 1/2 + 10= 11 +5 = 16
16+1/2 = 16 1/2
Answer:
3(x-2)+x=4x+6
Step-by-step explanation:
case 1) we have
3(x-2)+x=4x-6
Solve for x
3x-6+x=4x-6
4x-6=4x-6
0=0 ----> is true for any value of x
therefore
The equation has infinite solutions
case 2) we have
3(x-2)+x=2x-6
3x-6+x=2x-6
4x-2x=-6+6
2x=0
x=0
case 3) we have
3(x-2)+x=3x-3
3x-6+x=3x-3
4x-3x=-3+6
x=3
case 4) we have
3(x-2)+x=4x+6
3x-6+x=4x+6
4x-4x=6+6
0=12 ------> is not true
therefore
The equation has no solution